How the characteristics of research, development and innovation partnerships mediate their development - Acinas Garzon, Victor (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2022)
Whereas much has been written on the inter-organisational relations phenomenon from different bodies of literature such as strategy, innovation and management, it is typically done through variance studies built on major blind spots - single-party, single-level and single time conceptualization approaches - and rarely on the dynamics of inter-organisational relations. Hence, the motivation of this study is to enhance our understanding of inter-organisational relations development by overcoming these major blind spots in the literature and shedding light on the mechanisms which mediate their development. This study examines Research, Development and Innovation (RDI) partnerships focused on nanotechnology activities as they unfold over time by formulating the following research question: how can the characteristics of nanotechnology RDI partnerships mediate their development? In answering the research question, this study undertakes a longitudinal critical realism case study research method based on four cases consisting of two sets of polar cases within the emerging nanotechnology context. The main finding of this study is a co-evolutionary, multi-level mechanism-based explanation of how the characteristics in nanotechnology RDI partnerships can mediate their development. This finding contributes not only to inter-organisational relations theory in the area of RDI partnerships but also the innovation and strategy literature. Its significance is also underpinned by the novelty of the nanotechnology research context which is characterised by rapid technological change and the integration of knowledge from across different disciplines. In reaching this theoretical contribution, the study developed a structured and comprehensive research framework which integrates and extends previous research. This framework advances the application of critical realism by providing methodological guidance and illustrating in a contextualised step by step basis how to carry abductive and retroductive analysis through coding and analysis techniques which overcome criticisms to the commonly used grounded theory techniques.
An empirical study in the emerging area of nanotechnology
APPROVED
Keywords: alliances; alliance development; alliance dynamics; innovation; R&D; RDI; nanotechnology; critical realism; case study; Ph.D.; partnerships